Acute myocardial infarction secondary to mucormycosis after lung transplantation. (2021) - Naik, Chetan A.; Mathai, Susan K.; Sandkovsky, Uriel S.; Ausloos, Kenneth A.; Guileyardo, Joseph M.; Schwartz, Gary; Mason, David P.; Gottlieb, Robert; Grazia, Todd J.
Abstract: We present a case of a 57-year-old man who underwent bilateral lung transplantation for idiopathic pulmonary fibrosis. His immediately post-operative course was complicated by fever and cardiac arrest. Despite supportive care and broad-spectrum antibiotics, he experienced continued clinical decline. Autopsy results indicated angioinvasive mucormycosis and coronary arteritis resulting in acute myocardial infarction as the cause of death.